Features of development software for teaching secondary school students the Internet security - D. V. Stolbov (Academy of Cognitive and Natural Sciences, 2015)
This paper highlights the main aspects in development of software for teaching secondary school students the Internet security. The paper shows features of design the software. The research focus: to define features of design the software for teaching secondary school students the Internet security. Goals of study: to review programming learning tools for teaching pupils the Internet security; to determine the character of pupils' activity in the Internet; to define the features of design the software for teaching secondary school students the Internet security. Object of the study: the learning process of secondary school students. Subject of the study: the development of the software for teaching secondary school students safety in the Internet. The research methods: study of researches about teaching pupils the Internet security and design programming learning tools. The results of the study: the programming learning tools for teaching pupils the Internet security were reviewed; the character of pupils' activity in the Internet was determined; the features of design the software for teaching secondary school students the Internet security was defined. The conclusion: during the design the software for teaching secondary school students the Internet security is important to take into account age characteristics of the students, features of their activity in the Internet. Moreover requirements to computing learning tools must be included in development the software.